Digital Marketing Training for MSMEs to Increase Marketing Channel of Local Banten Product - Septariawulan Kusumasari; Fitria Riany Eris; Yudi LA Salampessy; Anggoro Suryo Pramudyo; Ratna Mega Sari; Bayu Meindrawan; Vega Yoesepa Pamela; Winda Nurtiana; Nezly Nurlia Putri; Karmelia Nurrohmah (EQUATOR SINAR AKADEMIA, 2022)
This community service activity is a digital marketing training conducted by a lecturer of Food Technology Study Program, Sultan Ageng Tirtayasa University to the people of Ciborang Village, Kadubeureum Village, Pabuaran District, Serang Regency. The purpose of this service activity is to provide training and practical knowledge of management knowledge in helping the people of Ciborang Villages represented by MSMEs Karisma Creativa, to improve the marketing of Banten local products with digital marketing strategies. The methods used are survey and direct material delivery, as well as simulations and discussions on digital marketing strategies. The results obtained were that the people of Ciborang Village, especially MSMEs Karisma Creativa member, were very enthusiastic in training and discussions. The results of this training are expected that the people of Ciborang Village, especially MSMEs Karisma Creativa, can optimize the use of the marketplace as a marketing tool to Increase Marketing Channel of Local Banten Product.